CORAL FISH DIVERSITY IN THE MARINE WATERS OF CENTRAL TAPANULI REGENCY - Hasan Sitorus; Kimberly Febrina Kodrat (CV. Radja Publika, 2025)
This study aims to identify and analyze the diversity of coral fish in the marine waters of Central Tapanuli Regency, which includes the areas of Mursala Island, Binasi Beach, and Pandan Waters. The method used is a qualitative approach with field observation, visual identification of species, and interviews with coastal communities. The results showed that there were 35 species of reef fish from 12 families identified, with Mursala Island being the location with the highest diversity. The dominant families include Pomacentridae, Chaetodontidae, and Labridae. Variations in diversity between locations are influenced by coral reef conditions, human activities, and the quality of the aquatic environment. Population declines of some reef fish species were also identified, which were related to environmentally unfriendly fishing practices and habitat degradation. These results reinforce the importance of sustainable management of marine resources by involving local communities as the main actors of conservation. This research provides an initial overview of the potential for marine biodiversity in Central Tapanuli and is the basis for coral reef ecosystem conservation policies in western Indonesia.